Comparison of BER between conventional, LDD and MMSE detector in DS-CDMA system - 449873 Raja Ati Nor Zainon Raja Azman Shah (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Telecommunication)) - Universiti Teknologi Malaysia, 2003